2015
DOI: 10.1038/bmt.2015.181
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of post-engraftment invasive fungal disease in adult allogeneic hematopoietic stem cell transplant recipients receiving oral azoles prophylaxis

Abstract: Studies that analyze the epidemiology and risk factors for invasive fungal disease (IFD) after engraftment in alloSCT are few in number. This single-center retrospective study included 404 alloSCT adult recipients surviving 440 days who engrafted and were discharged without prior IFD. All patients who received ⩾ 20 mg/day of prednisone were assigned to primary oral prophylaxis (itraconazole or low-dose voriconazole). The primary end point was the cumulative incidence (CI) of probable/proven IFD using the Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
1
28
1
Order By: Relevance
“…12,14 In this regard, we previously reported that low-dose voriconazole was clearly insufficient to prevent IFD compared to full dose in allo-HSCT recipients. 7 As a result of this high incidence of IFD, since January 2017, we changed our antimold prophylactic strategy to posaconazole 300 mg daily.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 In this regard, we previously reported that low-dose voriconazole was clearly insufficient to prevent IFD compared to full dose in allo-HSCT recipients. 7 As a result of this high incidence of IFD, since January 2017, we changed our antimold prophylactic strategy to posaconazole 300 mg daily.…”
Section: Discussionmentioning
confidence: 99%
“…GVHD occurring before day 100 after allo‐SCT was classified as acute GVHD, whereas that occurring after day 100 after allo‐SCT was classified as chronic GVHD . Both acute and chronic GVHD were evaluated according to the standard classifications published elsewhere . All patients were assessed for the following recently identified risk factors for pulmonary IFD after allo‐SCT; age (40 years), previous episode of allo‐SCT, persistent neutropenia, extensive chronic GVHD, and reactivation of cytomegalovirus.…”
Section: Methodsmentioning
confidence: 99%
“…Both acute and chronic GVHD were evaluated according to the standard classifications published elsewhere . All patients were assessed for the following recently identified risk factors for pulmonary IFD after allo‐SCT; age (40 years), previous episode of allo‐SCT, persistent neutropenia, extensive chronic GVHD, and reactivation of cytomegalovirus. Based on the total number of these factors, patients were classified as low risk (<1 factor), intermediate risk (two factors), or high risk (>3 factors).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, no differences have been found in outcome after IFI, with a similar mortality rate after UCBT or transplant with other stem cell sources ranging from 7% to 86% 13,21,30,32,36,41,43…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…Described incidence varies among different transplantation centers depending on many factors such as the geographical region, patients diagnosis, conditioning, period of neutropenia and type of primary prophylaxis 7,12,13,14,21,30,32,36,37,3943…”
Section: Fungal Infectionsmentioning
confidence: 99%